Application of Financial Literature through the Love of Saving Early at Elementary School, Oenesu Village - Lyra Ruchiyat Permata; Agustina Melyanti Dolu; Benyamin Yusuf Tae; Bernadeta Apriliani Tanggur; Bernadeta H. Palma Unggas; Mikhael A. Roncalli Kloa; Natalia Christin Hari; Sandro Mario Agun; Viany Cecilia Pah; Yoseph Mariano Meme; Filbrino Acuan Beda; Theofilus Woi; Elfandi Jodison Bani; Fransiskus H. Kaki Doy; Josep Rinaldo Nahak; Alfry Aristo Jansen Sinlae (Asian Journal of Community Services, 2022)
Socialization activities like saving are carried out by students participating in real work colleges thematic Universitas Katolik Widya Mandira aims to educate and provide an understanding of financial literacy through saving from an early age while increasing participants ' awareness and interest learn to save. Saving means setting aside some of the money you have to save and is one way to manage money, and familiarize participants educate to buy school necessities such as uniforms, stationery, and textbooks, and can help the family's economy from savings. This activity is one of the applications of knowledge carried out at the Nait State Elementary School and the GMIT Oenesu Elementary School which is carried out face-to-face while still adhering to health protocols. The methods used are lectures with extension techniques, using language and fun ways according to their age level, asking questions, and being creative in their work. practice make a piggy bank using used bottles and origami paper. The results of this activity, participants students gain knowledge about the benefits of saving and caring for the environment by utilizing household waste. This activity is expected to be continued by the school and also in the environment community so that these good habits can have a lasting impact for a better future